Tunable zero and first sounds in ultracold Fermi gases with Rabi coupling. (20th April 2017) - Lepori, L; Salasnich, L
Abstract: We consider a weakly-interacting fermionic gas of alkali-metal atoms characterized by two hyperfine states which are Rabi coupled. By using a Born approximation for the repulsive interaction we determine the zero-temperature equation of state of this Fermi gas in D spatial dimensions ( D   =  1, 2, 3). Then, adopting the Landau–Vlasov equation and hydrodynamic equtions, we investigate the speed of first sound and zero sound. We show that the two sounds, which occur respectively in collisional and collisionless regimes, crucially depend on the interplay between interaction strength and Rabi coupling. Finally, we discuss for some experimentally relevant cases the effect of a trapping harmonic potential on the density profles of the fermionic system.